Altitudinal gradient and its influence on the edofoclimatic characteristics of tropical forests - Murga-Orrillo, Hipolito; Coronado Jorge, Manuel Fernando; Abanto-Rodríguez, Carlos; Lobo, Francisco De Almeida (Instituto de Ecología, A.C., 2021)
Altitudinal gradients can generate environmental limits, influencing the growth and development of plant species. The aim was to understand the edaphoclimatic variation in altitudinal gradients, and its influence on tropical forests. Research articles with a geographic scope between 27º N and 27º S latitude were searched, with influence of altitudinal gradients between 0 m and 5000 m; The information was systematized, organizing it in climatic issues, in physicochemical and biological properties of the soil, and in the behavior of forest species. It was determined that the mean annual temperature (TMA) decreases as the altitude increases, and the annual precipitation (PA) presents maximum pluvial at mid altitudes; soil pH values decrease up to 3000 m, increasing above this altitude; however, organic matter, organic carbon, total carbon (TC), total nitrogen (NT) and the C/N ratio of the soil increase up to 3000 m a.s.l., above this altitude the values decrease; potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), and aluminum (Al) in the soil decrease with increasing altitude due to the influence of low temperatures and soil moisture (HS). The edaphoclimatic variation in the altitudinal gradients interacts with the forest species, affecting the physiological responses, decreasing their growth and height with increasing altitude; in the same way its density and diversity decreases with increasing altitude. The forest species of the tropics thrive in wide or narrow elevational and edaphoclimatic limits, so identifying these limits is essential not only in ecological terms, but also in political and economic terms, to design effective land use and conservation policies.